Rancangan Kansei Engineering System (KES) untuk Optimasi Hasil Pencarian Berdasarkan Kategori Emosi - Euis Nurlaelasari; Eko Pramono (LPPM Universitas Bina Sarana Informatika, 2023)
The design of a product will greatly influence a person's interest in the product and provide an overview of the impression of the product. Kansei Engineering is a method of determining product design based on feelings or emotions. The design of the product will be translated into human emotions. A brightly colored plate with a flower shape can be interpreted as a joyful emotion. This makes humans have an attachment to the product because of the emotional connection. Therefore, this research will implement the Kansei engineering method for products in e-commerce. This goal is motivated by e-commerce trends that will continue to develop in the future. The results of this study are the design of the Kansei system for searching products in e-commerce catalogs based on emotion. The conclusion of this research is to develop the best emotion-based product search algorithm and design the Kansei system with the main function of emotion-based product search. Based on the results that have been obtained, further research is expected to use a certain algorithm to automate the knowledge base processing which is very much needed in KES.